FAMILY CAREGIVING AND ALL-CAUSE MORTALITY: A META-ANALYSIS OF 12 LONGITUDINAL POPULATION-BASED STUDIES. (11th November 2018) - Mehri, N; Kinney, J; Rajabi Rostami, M
Abstract: The healthy caregiver hypothesis posits that positive aspects of family caregiving explain caregivers' lower mortality rates and better physical functioning. However, across longitudinal population-based studies, empirical support for this hypothesis is inconclusive. Using the random-effects meta-analysis model, we investigated the pooled effect of family caregiving on all-cause mortality among 12 longitudinal population-based studies consisting of seven US and five international (UK, Northern Ireland, Japan) studies. The studies investigated a total of 2, 685, 347 individuals including 414, 797 caregivers (15.4%) and 2, 270, 550 (84.5%) non-caregivers over an average of 9 years. A total of 118, 533 deaths occurred (2.6% of caregivers; 4.7% of non-caregivers). All-cause mortality was statistically lower among caregivers compared to non-caregivers in seven studies and non-significant in the remaining five studies. Results showed that the pooled effect of family caregiving on all-cause mortality across the 12 studies was statistically significant among caregivers: caregivers have 15 percent lower mortality compared to non-caregivers (HR=0.85; 95% CI:0.76, 0.95). The subgroup analysis revealed that the relationship between family caregiving and mortality was statistically non-significant among the US studies (HR=0.91; 95% CI: 0.80, 1.04). In contrast, the mortality rate was 33% lower in favor of caregivers among the international studies (HR=0.77; 95% CI: 0.73, 0.81). In conclusion, the results of this meta-analysis did not provide sufficient evidence to support the healthy caregiver hypothesis among the US studies. Future studies are needed to examine the effects of theoretically relevant micro- (e.g., kinships tie, length and type of caregiving) and macro- (e.g., social policy) characteristics that affect caregivers' all-cause mortality.